Non Genetic Therapeutic Approach to the Muscular Dystrophies - Samee, Tahseen; Al Hasan, Suzon; Tabassum, Muhatarima (Journal of Chittagong Medical College Teachers’ Association, 2010)
Keywords: muscular dystrophies; therapy DOI: 10.3329/jcmcta.v20i2.5625 Journal of Chittagong Medical College Teachers' Association 2009: 20(2):39-47